Markov-Switching Procedures for Dating the Euro-Zone Business Cycle - Hans-Martin Krolzig (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
This paper addresses the issues of identification and dating of the Euro-zone business cycle by using the Markov-switching approach innovated by Hamilton in his analysis of the US business cycle. Regime shifts in the stochastic process of economic growth in the Euro-zone are identified by fitting Markov-switching models to aggregated and single-country Euro-zone real GDP growth data of the last two decades. The models are found to be statistically congruent and economically meaningful. Based of the smoothed regime probabilities from the Markov-switching models the Euro-zone business cycle is dated and recessions from 1980Q1 to 1981Q1 and 1992Q3 to 1993Q2 are revealed. A Markov-switching vector autoregression of real GDP growth rates in eight EMU member states shows that while the business cycles in the Euro-zone have not been perfectly synchronized over the last two decades, the overall evidence for the presence of a common Euro-zone cycle is strong. – – Zur Identifikation und Datierung des Konjunkturzyklus in der Eurozone wird der von Hamilton zur Analyse des US-Konjunkturzyklus vorgeschlagene Markov-Regimewechselansatz auf vierteljährliche aggregierte und länderspezifische Zeitreihen des realen Bruttoinlandsproduktwachstums der zwei letzten Jahrzehnte angewandt. Mit den statistisch kongruenten und ökonomisch sinnvollen Modellen werden Regimewechsel im stochastischen Wachstumsprozess der Wirtschaft in der Eurozone identifiziert. Basierend auf den implizierten geglätteten Regimewahrscheinlichkeiten kann eine Datierung des Konjunkturzyklus in der Eurozone vorgenommen werden: Konjunkturzyklen in der Eurozone nicht perfekt ist, können mit der Ausnahme von Finnland für jedes Land simultane Regimewechsel in der mittleren Wachstumsrate identifiziert werden.
Keywords: 330; Konjunktur; Schock; Konjunkturzusammenhang; Markovscher Prozess; VAR-Modell; Eurozone; EU-Staaten